MENGKOMUNIKASIKAN DIRI ALLAH TERHADAP CIPTAAN SEBAGAI DASAR PEWARTAAN KAUM AWAM MELALUI MEDIA KOMUNIKASI SOSIAL - Banusu, Yeremias (Seminari Tinggi St. Fransiskus Xaverius Ambon, 2019)
Everyone who has been baptized in the Catholic Church is united with thebody of Christ and entitled to the grace of salvation from God. The salvationis God himself who has been communicating in the hidden self of humanbeing. Besides of obtaining salvation, a member of a Church is also obligedto carry out the task and vocation according to the vision and mission of theChurch. Jesus’ command is preaching salvation to all nations, mandated toeveryone who has been obtaining salvation. The laity as members of Christ’sbody is obliged to carry out the tasks mandated by Jesus. It is important for the laity because they are the one who are facing the world in the front line. Laymen have worldliness that stands out because they discharge all the dutiesand professional world. The development of today’s world that gives avariety of choices, challenges and opportunities force the laity in determiningtheir behavior. Positive and negative aspects are mix into one affecting theworld and everyone too. The laity may be affected by the situation of thetimes, but should not forget the basic calling and mission in the world. Thisstudy recast the concept of thinking that leads to practical pastoral action oflaymen in the use of social media communications for vocation and missionin the world. Through the library research, the views and teachings of theCatholic Church is dug to see how a Catholic laymen can carry out theirmission, through social modern communication on the self-communication ofGod in Jesus. In addition, they laity make create communication made byJesus Christ as the plenary communicator as basis for the communicationwith the world through social media communication. Social media communications are diverse and sophisticated these days, that can be a soft tool to beused by the laity in carrying out his mission. However, these media users need togain an understanding and deep concern because in addition to benefits, mediacommunications can also be an obstacle to the proclamation of God's truth. Hence,the laymen have to imitate Jesus’ way of communication as the plenaryCommunicator which is the core of God's self-communication to the creation.